(untitled) (Ameghiniana, 2013)
A specimen of Velizia inconstants Césari & Hünicken (gymnospermous leaf) found in the Cerro Agua Negra Formation, Río Blanco Basin, Argentina, extends the geographic range of the taxon to another sedimentary basin.